Authentication of the protected designation of origin “Kaki Ribera del Xúquer” from its mineral profile - Mir-Marqués, Alba; Cervera, María Luisa; de la Guardia, Miguel (Ciencia, 2016)
Protected designation of origin (PDO) “Kaki Ribera del Xúquer” samples were discriminated from those produced in other five origins concerning: towns surrounding Valencia, Alicante, Andalucía, Castellón and also Ribera, produced outside the PDO frame. Multivariate analysis tools; such as principal components analysis (PCA), hierarchical cluster analysis (HCA), linear discriminate analysis (LDA) and classification and regression trees(CARTs) were evaluated in order to achieve a correct sample classification of the six sample origin groups considered. Chemometric analysis was conducted with 14 variables (content of different elements in mg kg-1, determined by ICP-OES and ICP-MS). HCA and CART cannot authenticate the origin of kaki fruits at 100 %; CART provided a separation of 79 % for the PDO samples. PCA only discriminated well the samples as a function of their different harvest but LDA provided quite satisfactory results obtaining a classification rate of 100 % for samples ofthe calibration set and 67 % for those included in the validation set.